Sistema de gestión de desechos lubricantes en la Micro Empresa Electro-Service del barrio San Felipe, una contribución a la disminución del impacto ambiental. - Bracho Pasquel, Pablo Andrés (2018)
The purpose of the research project is the design of a lubricant waste management system in the micro-enterprise Electro-Service of the San Felipe neighborhood, which will contribute to the reduction of the environmental impact of the sector, due to the production of waste from this sector. place, which has grown significantly thanks to the increase in jobs dedicated to automotive mechanics in general, is that approximately 20 small companies are dedicated to this activity, which do not have an environmental management system, aspect that aggravates environmental pollution , specifically the causes of the Yanayacu River, because of the discharges of the used lubricants. To establish the design parameters of the lubricant waste management system, the hypothetical deductive method will be used, which will allow logical consequences, based on general knowledge, through observation of the workplace of the microenterprise. To characterize it, it is necessary to prepare a SWOT Matrix and a survey addressed to the service personnel of Electro-Service, in order to know the state in which the entity is operating, which evidenced that there is currently no management system of lubricant waste, therefore the improper handling of the same, representing a risk to the environment and the health of the personnel that handles this type of waste. Through the Leopold Matrix, a negative impact of -7 / + 7 was obtained, due to the productive activity in the soil, water and air factors. Once the current situation of the microenterprise has been defined, a lubricant waste management system based on the ISO 14001: 2015 Standard is proposed, which allows the correct management and storage of the lubricant waste.